Financial Development and Economic Growth: Evidence from Nepal - Paudel, Ramesh C.; Acharya, Chakra Pani (NRB Economic Review, 2020)
This paper aims to examine the role of financial development and economic growth in Nepal employing Autoregressive distributed lag (ARDL) approach of cointegration using time series data for the period from 1965 to 2018. Nepal is a unique country with big markets in the neighbors-India and China but remains as one of the poor landlocked developing countries, even being the earlier entrant in liberalization and reform. Nepal recently went through a substantial political transition and now the stable government is seeking substantial amount of foreign direct investment. In this background, it will be better, for a good policy analysis, to know how the financial activities have played the role in highly intended economic growth. We develop a model with five proxies of financial development (broad money, domestic credit to private sector, total credit from banking sector, capital formation, and foreign direct investment); and econometrically test their contribution in economic growth. Overall, the results suggest that financial development causes to economic growth substantially, except in the case of foreign direct investment. This result warns the policy makers to be more serious making investment friendly economy to attract the expected foreign direct investment.